Use of Authentic Texts in Literacy and Reading Practices Mediated by the Google Arts and Culture App (Interdisciplinary Studies Journal, 2024)
The study addresses literacy from the perspective of digital technologies, discussing the use of authentic texts from the Google Arts and Culture app for literacy (SOARES, 2004; FREIRES; MORGADO; BENTO, 2022). The objective is to analyze the authentic texts from the Google Arts and Culture app as a contribution to literacy and reading, serving as a bridge between school and society in terms of using digital technologies in the early years of elementary education. It is a qualitative study (FÁVERO; PINHEIRO; SARTORI, 2023). The method is a case study, and the data collection is through structured observation (FONTANA; ROSA, 2023). Data analysis is done through content analysis (BARDIN, 2016). The results indicated that it is possible to use the authentic texts from the aforementioned digital technology in literacy, and it is important to create a didactic guide that presents the characteristics and how to use the app in literacy, especially for teachers who are not familiar with digital technologies.
Keywords: Literacy and Reading; Educational Technologies; Authentic Texts